Fish waste Utilization with Reference to Fish Protein Hydrolysate – A Review - Wangkheirakpam, M. R.; Mahanand, S. S.; Majumdar, R. K.; Sharma, S.; Hidangmayum, D. D.; Netam, S. (Fishery Technology, 2019)
Aquaculture and capture fisheries have contributed to the global economy for decades, supporting livelihood as well as nutritionall status. The sector has been growing substantially that more than 60% by-products as waste are generated which includes skin, head, frames, fins and viscera. With an increasing population with limited resource and food supply, the need for utilizing the discarded waste have added interest in many processing industries. This review discusses on hydrolysis of un-utilised fish and fish waste which are rich source of nutrient that can impart stability in food products, possess noble pharmaceuticals and neutraceuticals significance to health. Fish protein hydrolysate has attracted much attention as an excellent source of bioactive peptides imparting antioxidant, antihypertensive, immunomodulatory and antimicrobial properties with a good balance of essential amino acids. Above all, the review also reveals the present status and future potential of utilizing fish waste into economically and sustainable products for human consumption.